Enzyme-catalysed improved resolution of (RS)-4-cyano-4-(3,4-dimethoxyphenyl)-4-isopropyl-1-butanol - Im, DS; Cheong, CS; Lee, SH; Park, H; Youn, BH (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Resolutions of (RS)-4-cyano-4-(3,4-dimethoxyphenyl)-4-isopropyl-1-butanol 1 using various enzymes were performed. Among them, Pseudomonas fluorescens resolved it with moderate stereoselectivity (E=13) and reacted faster with the (S)-enantiomer. To optimize enzyme-catalysed reaction conditions for the resolution, the effect of solvents and additives was studied. In n-hexane:ethyl acetate (9:1), both reaction rate and selectivity were high. When pyridine, potassium carbonate and molecular sieves were used as additives, the enantiomeric excess of the (R)-enantiomer was 99, 99 and 98% at 52-60% conversion, respectively. However, in diisopropyl ether, the enantiomeric excess of unreacted alcohol (R)-1 was up to 99% at 70% conversion without additives. (C) 1999 Elsevier Science Ltd. All rights reserved.